Risk factors for incidence of rotator cuff syndrome in a large working population - Julie Bodin; Catherine Ha; Audrey Petit Le Manac'h; Celine Sérazin; Alexis Descatha; Annette Leclerc; Marcel Goldberg; Yves Roquelaure (Nordic Association of Occupational Safety and Health (NOROSH), 2012)
OBJECTIVES: The aim of this study was to assess the effects of personal and work-related factors on the incidence of rotator cuff syndrome (RCS) in a large working population. METHODS: A total of 3710 French workers were included in a cross-sectional study in 2002-2005. All completed a self-administered questionnaire about personal factors and work exposure. Using a standardized physical examination, occupational physicians established a diagnosis of RCS. Between 2007-2010, 1611 workers were re-examined. Associations between RCS and risk factors at baseline were analyzed by logistic regression. RESULTS: A total of 839 men and 617 women without RCS at baseline were eligible for analysis. RCS was diagnosed in 51 men (6.1%) and 45 women (7.3%). The risk of RCS increased with age for both genders [odds ratio (OR) 4.7 (95% confidence interval [95% CI] 2.2-10.0) for men aged 45-49 years and 5.4 (95% CI 2.3-13.2) for women aged 50-59 years; reference <40 years]. For men, the work-related risk factors were repeated posture with the arms above the shoulder level combined with high perceived physical exertion [OR 3.3 (95% CI 1.3-8.4)] and low coworker support [OR 2.0 (95% CI 1.1-3.9)]. For women, working with colleagues in temporary employment [OR 2.2 (95% CI 1.2-4.2)] and repeated arm abduction (60-90°) [OR 2.6 (95% CI 1.4-5.0)] were associated with RCS. CONCLUSIONS: Age was the strongest predictor for incident cases of RCS, and arm abduction was the major work-related risk factor for both genders. Lack of social support was a predictor for RCS among men.